The Law Enforcement on Crime of Motorcycle Theft - Hamdani Marsiawan; Sri Endah Wahyuningsih; Bambang Tri Bawono (Law Development Journal, 2022)
The purpose of this research is to discuss the problems: How to Enforce the Criminal Act of Motorcycle Theft and How to Efforts to Combat the Crime of Motorcycle Theft. In this research, the method used was an empirical juridical approach. The conclusion of this study is the Law Enforcement of the Crime of Motorcycle Theft. Criminal was arrested, detained in the detention center by investigators then extended by the Public Prosecutor, so that having read the Decree of the Head of the District Court regarding the Appointment of the Panel of Judges, assembly. The judge determines the day of the trial, examines the case file, other relevant documents, hears the statements of the witnesses and the defendant's statements and pays attention to the evidence submitted at trial, then hears the reading of the criminal charges submitted by the public prosecutor. Efforts to Combat the Crime of Motorcycle Theft by carrying out preventive efforts, namely efforts that are still at the level of prevention before an act occurs by conducting socialization or counseling to the community in order to increase public legal awareness. Provide information to the public in the event of a motorcycle theft crime to immediately report it to the authorities. Repressive efforts when a crime has occurred by taking action against the perpetrators of the crime in accordance with the actions committed. In connection with the prosecution process that has been carried out by the perpetrators, the police have taken legal action in the form of arrests, detentions and the process of delegating cases to court. If the perpetrator is proven guilty, the judge will give a sentence in accordance with the demands of the Public Prosecutor or based on the consideration of the Deliberation of the Panel of Judges to be brought to the Correctional Institution to serve his criminal period.